Measurement of the W boson mass with the D0 detector - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Sman, B.; et al. (American Physical Society (APS), 2012)
We present a measurement of the W boson mass using data corresponding to 4.3fb -1 of integrated luminosity collected with the D0 detector during Run II at the Fermilab Tevatron pp̄ collider. With a sample of 1677394 W→eν candidate events, we measure M W=80.367±0. 026GeV. This result is combined with an earlier D0 result determined using an independent Run II data sample, corresponding to 1fb -1 of integrated luminosity, to yield M W=80.375±0.023GeV. © 2012 American Physical Society.
Keywords: Collider; Data sample; Fermilab Tevatron; Integrated luminosity; Luminance; Bosons